Experiencing elementary science - Neuman, Donald B. (Wadsworth Pub. Co., 1993)
In Experiencing Elementary Science, Neuman helps pre-service and practicing teachers make the difficult transition from theory to practice. By describing new learning and teaching theories in an applied, experiential context, Neuman helps students learn to use strategies that derive from learning theories